Bounded rationality in a P2P lending market. (23rd April 2020) - Kim, Dongwoo
Abstract : Purpose: This study seeks to provide a systematic analysis of bounded rationality expressed by individual lenders in a Peer-to-peer (P2P) lending market. Design/methodology/approach: 26, 383 personal loan listings collected from Moneyauction in Korea, were analyzed with binary logit regression. 6 hypothesis based on bounded rationality theory were constructed and tested. Binary logit regression was employed as both dependent variables have binary characteristics and can thus be assigned values equal to 0 or 1. Findings: The results confirm that individual P2P lenders make their funding decisions based on bounded rationality, arousing from cognitive limitations, incomplete information, and time constraints. Research limitations/implications: By adopting the theory of bounded rationality, this study attempts to prepare the theoretical background for an explanation of the decision behavior of individual lenders in a P2P lending market. Practical implications: The findings of this research emphasize the importance of the platform provider's role to facilitate the sustainable market growth of P2P lending as an alternative form of finance. As the rationality of individual lenders is bounded during their decision-making process according to the research findings, the platform provider must continuously adjust their decision criteria by referencing the cumulative loan repayment data. Originality/value: This study attempts to identify for the first time the suboptimal decision making by individual lenders in a P2P lending market on the basis of bounded rationality theory.